Treatment landscape and prognosis after treatment with trastuzumab emtansine - Laakmann, Elena; Wallwiener, Markus; Schneeweiss, Andreas (Geburtshilfe und Frauenheilkunde, 2020)
Pertuzumab and T-DM1 are two efficient anti-HER2 treatments for patients with HER2-positive advanced breast cancer. While pertuzumab is usually given in first-line treatment and T-DM1 in second-line treatment, standard therapy options seem to be exhausted up to now after the treatment of patients with these two therapy options. Therefore, it is important to have data that describes the therapy situation and prognosis after T-DM1 treatment. Methods The PRAEGNANT metastatic breast cancer registry (NCT02338167) is a prospective registry for breast cancer patients with a focus on molecular biomarkers. Patients of all therapy lines with any kind of treatment are eligible. Collected data comprises therapies, adverse events, quality of life and other patient reported outcomes. Here we report on the patient characteristics and descriptive prognostic data for HER2-positive patients who have completed a treatment with T-DM1. Therapy patterns after T-DM1 and progression-free survival are reported as well as overall survival. Results A total of 85 patients were identified for the study who were prospectively observed during therapy after the termination of T-DM1. The main reason for T-DM1 termination was progress. Following T-DM1, lapatinib, trastuzumab and chemotherapy were the main therapy choices. Median progression-free survival was 4.8 months (95% CI: 3.2 - 6.3) and median overall survival was 18.4 months (95% CI: 15.5 - 21.3). Conclusions Therapy options after T-DM1 in a real-world setting seem to exhibit a relevant clinical efficacy, supporting the concept of continuous anti-HER2 treatments in the advanced therapy setting for breast cancer patients. Novel therapies are needed to improve the rather short median progression-free survival.
Gesehen am 11.01.2021